The Influence Of Trust And Service Quality On Customer Satisfaction In Scholarship Partner Insurance Products (Case Study Of Ajb Bumiputera 1912 Rantauprapat Branch) - Imsar; Atika; Lestari, Ayu (ProBisnis : Jurnal Manajemen, 2024)
This research aims to determine the influence of trust and service quality on customer satisfaction with Ajb Bumiputera scholarship partner insurance products 1912 Rantauprapat branch. Research that uses a quantitative approach. Data collection techniques and instruments use scale model questionnaires likert taken from a sample of 76 respondents. In data processing research using the SPSS Release 26.0 For-Windows application. From the results Statistical analysis shows that there is a positive and significant influence partial that the two independent variables are trust (X1) and service quality (X2) has a significant effect on the dependent variable. Simultaneous test results F The obtained F-count value > F-table and significant < 0.05 then trust (X1), and service quality (X2) simultaneously or simultaneously has a significant effect on customer satisfaction (Y). Based on the results of the adjusted R determination test square is 0.243, this means the ability of the trust variable (X1) and quality service (X2) is able to explain the satisfaction variable (Y). The implications dominant in research regarding the variable quality of services provided the company Ajb Bumiputera 1912 Rantauprapat Branch to customers not yet optimal, it is hoped that in the future good service will need to be improved such as: having an attitude of responsibility or keeping promises, serving with a smile and being humble, behaving sympathetically, politely, and honestly are the attention of regular customers stay or decide not to be part of the company. With Thus, good or bad service quality depends on the provider's capabilities services to meet customer expectations absolutely.